Metabolite Profiles of Sukabumi Arabica Green Coffee Beans Evaluated by 1H NMR-Based Metabolomics - Hamdani, Ahmad; Happyana, Nizar (Molekul, 2024)
Although Sukabumi arabica coffee is one of the famous coffees in Indonesia, however its chemical information is still limited in the literature. In this work, the metabolite profiles of arabica green coffee beans obtained from various plantations in Sukabumi, including Ciayunan, Pondok Halimun, and Selabintana were evaluated by 1H NMR-based metabolomics. In total, 19 metabolites were successfully identified, including the major and minor metabolites of the coffee. The score plot of the OPLS-DA (Orthogonal Partial Least Square Discriminant Analysis) model was successful in classifying the metabolite profiles of the coffees based on their origins. The loading plot analysis showed that the signals belonging to fatty acids, sucrose, trigonelline, chlorogenic acid, lactic acid, and quinic acid, contributed to the classification. S-plot analysis revealed that Selabintana coffee was characterized with higher concentrations of trigonelline and sucrose, whereas Ciayunan sample had higher levels of fatty acids. Meanwhile, the metabolite profile of Pondok Halimun coffee demonstrated an intermediate characteristic between the Ciayunan and Selabintana samples. This work provided valuable scientific information for coffee development especially in West Java and generally in Indonesia. Keywords: metabolomics, multivariate data analysis, NMR, Sukabumi arabica green coffee beans.